Altitudinal patterns of soil and microbial C:N:P stoichiometry in subtropical forests in Daming Mountain, South China - Huo, Chunlin; Zhang, Zhonghua; Luo, Yinghua; Hu, Gang (Frontiers in Earth Science, 2025)
IntroductionAltitude-induced variations in hydrothermal conditions and vegetation affect the carbon (C), nitrogen (N), and phosphorus (P) contents in both soil and microbial biomass. However, the specific patterns of changes in these nutrients and their stoichiometry in response to altitudinal changes remain unclear.MethodsIn this study, we analyzed the altitudinal patterns of soil and microbial biomass C:N:P stoichiometry across three soil layers (0–20, 20–40, and 40–60 cm) in the subtropical mountain ecosystems on Daming Mountain, South China.ResultsOur results revealed that soil C content and C:N ratio in the 0–20 cm layer initially increased and then decreased with increasing altitude. Meanwhile, soil P content in the 40–60 cm layer decreased. Soil microbial biomass P content initially decreased and then increased with altitude across all soil layers, whereas soil microbial biomass C:P and N:P ratios exhibited opposite trends. For soil and microbial biomass C:P and N:P ratios along the altitudinal gradient, soil microbial growth was mainly restricted by P, with this limitation being more pronounced at mid-to-low altitudes. Soil microbial biomass C, N, and P contents were positively correlated with soil C, N, and P contents and their ratios, available N (AN), available P (AP), and soil water content (SWC), but negatively correlated with soil bulk density, soil pH and soil temperature. In contrast, microbial biomass C, N, and P stoichiometric ratios exhibited the opposite or non-significant relationships with these factors. Notably, AN, AP, and SWC were the dominant factors affecting soil microbial biomass C:N:P stoichiometry.DiscussionThese findings contribute to the understanding of soil nutrient stoichiometry and their responses to environmental changes in subtropical mountain ecosystems.